(3GdeRgQ aj Ydhe GddZI hCfhGYgGs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCdSf hGddZGJ hSejJg HGdeRgQ ai Ydhe GddZI GdChd ai eYQaI GdaUjM GdKGHJ hGdKGfi ai eYQaI eGOhfg ef GddZI s
(3BNQgG (B:s
(3hGdCSQ (B: (3GdNdb , hGdgGOi (B: (3GdYfb , hGdCfhM (B: (3GdcKjQ GdRMjQ ai LQjg Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3UaMGJgG eLOhdI HGdPgHs
(3fSNI cJHJ HQSe GdbGVi VjGA GdOjf eMeO GdRQYi GdCfUGQi GdMfais
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs